Core-shell nanofibers as drug delivery systems - Zupančič Špela (Acta Pharmaceutica)
Core-shell nanofibers have grown in popularity over the last decade owing to their special features and their many applications in biomedicine. They can be produced by electrospinning of immiscible polymer blends or emulsions through a single nozzle or by electrospinning using a coaxial nozzle. Several of the electrospinning parameters allow great versatility for the compositions and diameters of core-shell nanofibers to be produced. Morphology of core-shell nanofibers can be investigated using transmission electron microscopy and, in some cases, scanning electron microscopy. Several studies have shown that core-shell nanofibers have some advantages over monolithic nanofibers, such as better drug, protein, gene or probiotic incorporation into the nanofibers, greater control over drug release, and maintenance of protein structure and activity during electrospinning. We herein review the production and characterization of core-shell nanofibers, the critical parameters that affect their development, and their advantages as delivery systems.